Epidemiological Study of Cryptosporidium parvum in Al- Diwaniyah province - Reim Hameid Al-Shepany; Najim Abd alwahad Al-Jadoa (Al-Qadisiyah Journal of Pure Science, 2018)
The present study aimed to investigate the parasite Cryptosporidium parvum in the children under 12 years old in the province of Al- Diwaniyah and know the impact of some epidemiological factors in the spread of the parasite.The study includes the test of 1177 samples of feces from children for the period from. 2012.11.1 up to.2013. 10.31. Acid fast stain was used for the detection of Cryptosporidium oocystes.The results of this study showed that the total infection rate of parasite reached ( 18.01% ) , with significant differences (P=0.003) during the months of infection with the highest rate of infection was recorded in the month of July (28.89%) and the lowest in the month of February(8.49%), Also recorded significant differences of infection for the age groups (P = 0.029) as it recorded the highest rate of infection among the age group (<1) amounting to( 21.52%) and lowest infection rate among the age group( 9-12) years as it was (10.79%) , also There is significant difference(P=0.281) betwee male and femal infection as the percentage of infection in the male (16.96%) while in the femal was ( 19.41%) , Also recorded significant differences according to the nature of the infection housing (P = 0.009) with`` the highest percentage of infection in rural (21.11%) and the lowest rate of infection was recorded in the city center (15.21%) , Also recorded significant differences for the presence of animals (p = 0.005) recorded the highest rate of infection in the people which have animals (cows) (21.64%) and the lowest rate of infection found in the people which do not have the animals (12.56%) , Also found that the parasite Entamoeba histolytica was the most parasite found with C. parvum.